Evaluation of the effectiveness and performance of environmental impact assessment studies in Greece - Papamichael, Iliana; Tsiolaki, Foteini; Stylianou, Marinos; Voukkali, Irene; Sourkouni, Georgia; Argirusis, Nikolaos; Argirusis, Christos; Zorpas, Antonis A. (Comptes Rendus. Chimie)
As environmental management is becoming increasingly complex, adequate assessment techniques must be utilized to forecast environmental impact trends. The current study aims to investigate the effectiveness of the evaluation system in Greece regarding environmental impact assessment (EIA) concerning projects. Data were extracted from literature and a questionnaire, which was distributed electronically on a Pan-Hellenic scale. Results indicated that the EIA system in Greece has solid foundations with a weak point regarding implementation. Strengths, weaknesses, and threats of EIA institution were analyzed through SWOT-AHP (Strength, Weaknesses, Opportunities, Threats and Analytical Hierarchy Process) analysis. A dominant criterion in the analysis due to the dynamic of the deep economic recession was found to be the economic crisis.